2015
DOI: 10.1016/j.reprotox.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary biomarkers of exposure to organophosphate insecticides and serum reproductive hormones in men from NHANES 1999–2002

Abstract: Exposure to organophosphate (OP) insecticides may alter reproductive hormone levels in men and increase the risk for poor reductive health and other adverse health outcomes. However, relevant epidemiology studies in men are limited. We evaluated urinary concentrations of OP metabolites (3,5,6-trichloro-2-pyridinol and six dialkyl phosphates) in relation to serum concentrations of testosterone (T) and estradiol among 356 men aged 20–55 years old from the U.S. National Health and Nutrition Examination Survey. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 47 publications
2
18
1
Order By: Relevance
“…Meeker et al (2006Meeker et al ( , 2007 [38,39] revealed the negative association between urinary metabolites of insecticides and testosterone, estradiol and free androgen index. Omoike et al (2015) [40] showed such associations only with testosterone. In contrast Melgarejo et al (2015) [37] revealed the positive association between urinary concentrations of organophosphate pesticide metabolites and LH and FSH.…”
Section: Organophosphate Pesticides and Male Reproductive Hormonesmentioning
confidence: 95%
See 4 more Smart Citations
“…Meeker et al (2006Meeker et al ( , 2007 [38,39] revealed the negative association between urinary metabolites of insecticides and testosterone, estradiol and free androgen index. Omoike et al (2015) [40] showed such associations only with testosterone. In contrast Melgarejo et al (2015) [37] revealed the positive association between urinary concentrations of organophosphate pesticide metabolites and LH and FSH.…”
Section: Organophosphate Pesticides and Male Reproductive Hormonesmentioning
confidence: 95%
“…Due to extensive use of such pesticides, a large proportion of the population is exposed to these chemicals or their environmental degradation products. Four original papers referring to exposure to organophosphate pesticides and levels of reproductive hormones were included in the review [37][38][39][40]. Three of the studies were conducted in the USA [38][39][40] and one in Spain [37].…”
Section: Organophosphate Pesticides and Male Reproductive Hormonesmentioning
confidence: 99%
See 3 more Smart Citations